The production, molecular weight and viscosifying power of alginate produced by Azotobacter vinelandii is affected by the carbon source in submerged cultures (2015)
Alginate is a linear polymer composed of b-1,4 linked mannuronic acid and its epimer, a-L-guluronic acid, and frequently extracted from marine algae, as from bacteria such as Azotobacter and Pseudomonas. Here, we show the impact of conventional and unconventional carbon sources on A. vinelandii growth, alginate production, its mean molecular weight (MMW) and its viscosifying power. Starting with 20 g/L of sugars, the highest biomass concentration was obtained using deproteinized and hydrolyzed whey (6.67±0.72 g/L), and sugarcane juice (6.68±0.45 g/L). However, the maximum alginate production was achieved using sucrose (5.11±0.37 g/L), as well the highest alginate yield and specific productivity. Otherwise, the higher alginate MMW was obtained using sugarcane juice (1203±120 kDa), and the higher viscosifying power was obtained using deproteinized/ hydrolyzed whey (23.8±2.6 cps L/galg). This information suggests that it is possible to manipulate the productivity and molecular characteristics of alginates, as a function of the carbon source used. All this, together with the knowledge of the effects of environmental conditions will allow for high yields of high added value biopolymers.